Transformative community projects in East Germany's rural spaces: exploring more sustainable forms of learning, working, and living - Broecher, Joachim; Painter, Janet F. (Frontiers in Sociology, 2023)
Increasingly people experience alienation in educational institutions, in work life, and fragmentation in their personal life. This study explores more self-determined, healthy, and sustainable forms of working, learning, and living through a dynamic process that began in 2020 with the purchase of an old homestead in Eastern Germany. Through the remodeling of the buildings and grounds, the first social and cultural references emerged. Along with practical uses, the farm project sees itself as a future workshop or think tank. The resulting consideration includes ideas of compulsory schooling woven into a self-designed format and the introduction of an unconditional basic income. These components could lead to thousands of such projects in rural and urban areas. Drawing from communitarianism, the belief is that an active civil society must take on social, economic, and educational responsibilities and offer children and young people improved conditions in which to grow up. Theory development on the individual components exists, such as entrepreneurship, transformation, community-building, basic income, or self-directed learning but not on the interaction of these variables in the overall context. We tentatively call this integrated design a transformative community project.